Impact of tricuspid regurgitation and its postprocedural reduction on long term outcome in patients undergoing percutaneous mitral valve edge to edge repair. (25th November 2020) - Koell, B; Ludwig, S; Bhadra, O; Schofer, N; Schirmer, J; Conradi, L; Reichenspurner, H; Blankenberg, S; Lubos, E; Kalbacher, D
Abstract: Background: Prevalence of functional tricuspid valve regurgitation (TR) in the adult population is high and mostly considered as a consequence of left-sided heart failure. In patients with moderate-to-severe and severe mitral regurgitation (MR), relevant concomitant TR is found in about 30–50%. For many years the concept of a reduction of secondary TR after mitral valve surgery has been widely accepted. However, more recently, compelling data have shown that surgically untreated functional TR can persist or even worsen despite the correction of the associated left-sided lesion. In line with previous research, studies have indicated that preexisting concomitant TR is an independent predictor for adverse outcome in patients undergoing percutaneous mitral valve Edge-to-Edge Repair (pMVR). Purpose: This study intends to determine the extent to which the severity of tricuspid regurgitation, measured six months after pMVR, impacts the outcome. Methods: Between September 2008 and July 2018, 805 consecutive patients with moderate-to-severe or severe MR underwent pVMR therapy with the MitraClip device at our center. We exclude patients with missing date of follow-up (n=54) and patients with missing values for baseline tricuspid regurgitation (n=93). We analyze, therefore, data of 658 patients with a median follow-up time of 4.93 (4.2, 4.99) years. Severity of TR was evaluated at baseline and six months after pMVR. Results: Among 658 high-risk patients (mean age 75.4±8.7 years, 59.7% male, median STS Score 3.9 [2.4, 6.1]), 248 patients were suffering from no/mild (37.6%), 213 from moderate (32.6%) and 197 patients from severe (29.9%) TR. Functional MR was present in 429 (65.5%) patients. Procedural success was achieved in the majority of patients (no/mild TR 90.3%, moderate TR 91.1%, severe TR 90.4%). Overall, mortality rates up to two-year follow-up were highest for patients with severe TR (no/mild TR 30.2%, moderate TR 37.6%, severe TR 42.6%, p=0.023). The risk for overall mortality (Kaplan-Meier analysis, p=0.0027, Figure 1) was related to increasing TR severity. However, Kaplan-Meier analysis showed no relevant differences for the combined endpoint of death and rehospitalization (p=0.058). Interestingly, in a pairwise comparison, the risk for patients with pre-existing severe TR and postprocedural reduction to mild or moderate TR (n=17) was reduced for the combined endpoint (p=0.021) compared to patients with persistent severe TR (n=28). Conclusion: Moderate and severe TR in high-risk patients undergoing pMVR is associated with an increased risk for overall mortality. While preliminary, the presented data suggest a favorable outcome in patients with a postprocedural reduction in the severity of TR. The results of this study indicate the importance of developing new therapeutic strategies in high-risk patients with combined MR and TR, probably leading to concomitant tricuspid valve interventions. Funding Acknowledgement: Type of funding source: None